Green Tea (EGCG) Decreases Malondialdehide in Oxidative Stress Exposure to Psychological Stress - M. Dodi F Priaminda; Bambang Wirjatmadi; Bambang Purwanto; Merryana Adriani (Health Notions, 2018)
Exposure to psychological stress can cause oxidative stress. Provision of exogenous antioxidants is expected to reduce the occurrence of oxidative stress. Green tea with its active ingredient Epigalocatechin Galat is considered to reduce the occurrence of oxidative stress. The purpose of this study was to examine the administration of green tea (EGCG) on the effect decreasing MDA levels against Wistar Strain (Rattus norvegicus) white rats exposed to psychological stress; with Randomized Post Test design of only group design by grouping into 5 groups, with control group and treatment group. Administration of steeping green tea (EGCG) with a single dose. To find out the significant influence of the independent variable on a set of variable group tested Manova. Post hoc testing using LSD (Least Significance Different) was performed to see significant differences between groups. In this study, obtained MDA data with significant decrease at the 6th hours after consum EGCG. Keywords: oxidative stress; green tea, EGCG, malondialdehide